Development of an innovative grid ancillary service for PV installations: Methodology, communication issues and experimental results. (April 2021) - Tsiakalos, An.; Tsiamitros, D.; Tsiakalos, Ap.; Stimoniaris, D.; Ozdemir, A.; Roumeliotis, M.; Asimopoulos, N.
Abstract: In high Renewable Energy Sources (RES) penetration cases and especially whenever local grids are considered, the absence of coordination between RES production and demand includes the risk of reduced reliability of power supply to the consumers. In this paper, an innovative, cost-effective and easy to install technology is introduced that allows PV sun-tracking systems to regulate their actual energy production according to the network demands instead of relying on the inverters to manage the excessive energy. This method is suitable for existing applications where energy storage is not possible. In addition, a main advantage of the proposed method is that it protects the PV panels from high temperatures when network loads permits, expanding thus the life span of a system. This technology utilizes control-automation and communication tools, to adjust the PV power production of distributed sources with respect to the needs of the consumers as well as to the technical and economic requirements of the electricity grid and the power market. The main idea is to use the sun-tracking system, i.e. by changing the position of slave trackers, for achieving maximum power and to determine the unserved power, so that enables charging and market integration potential. The system can be adopted to almost all sun-tracking systems, whereas the signal transmission towards the PV system is accomplished by the newly-introduced and the cost-effective Digital Audio Broadcasting (DAB) energy data transmission protocol.